Administrative Improbity (Brazil) - Fridriczewski, Vanir; Rodríguez-García, Nicolás (EUNOMÍA. Revista en Cultura de la Legalidad, 2024)
Brazil, especially since the redemocratization brought about by the 1988 Constitution, has introduced important changes in its sanctioning law. Several bodies with sanctioning powers were created and a system with multiple areas of responsibility was established. One of these innovations refers to the so-called acts of administrative improbity, a peculiarity of the Brazilian legal-constitutional system, unparalleled at least in Western countries, which is directly related to the prosecution of public corruption. Therefore, this paper aims to examine the main aspects of this liability system, trying to provide the reader with an understanding of what type of wrongdoing is involved, its minimum legal regime, as well as the procedural tools to punish the practice of these acts, paying special attention to some nuclear points of this matter that have been introduced in a legislative reform of 2021.
Keywords: Fight Against Corruption; Brazil; Administrative Improbity